Audit Judgement : Faktor Tekanan Ketaatan, Kompleksitas Tugas, Dan Pengalaman Kerja (Studi Pada Kantor Akuntan Publik Di Jakarta Selatan) - Gita Ayu Andhiani Wulandari; Erwin Indriyanto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to investigate the impact of obedience pressure, task complexity, and work experience on audit judgment. The research sample involves 22 Kantor Akuntan Publik (KAP) or Public Accounting Firms, with 100 respondents from 10 KAPs approached directly and 12 KAPs contacted through email and Google Form via LinkedIn. The population of auditors in this study reached 381 individuals. The method for hypothesis testing used multiple linear regression analysis. The research results indicate that obedience pressure has a positive impact on audit judgment, while task complexity has a negative and significant impact on audit judgment. Meanwhile, work experience does not significantly affect audit judgment, indicating that changes in the level of work experience do not contribute to changes in audit judgment. This study provides further insights into the factors influencing audit judgment, with findings suggesting that obedience pressure and task complexity are crucial points to consider in enhancing the quality of audit judgment. Keywords : Obedience pressure, task complexity, work experience, audit judgment